Rzecz o potencjale dziecka w aktywnościach muzycznych – refleksje o „ruchu z muzyką” - Ewa Szatan (Problemy Wczesnej Edukacji)
Musical activities give the child a chance to meet higher needs (Maslow), including aesthetic ones (Wojnar). One of the activities is movement with music, in which children realize their musical and movement interpretations. They create creative situations and creation, but above all, they open the child to various challenges and release the potential inherent in him. In the text I will present my reflections based on selected situations that I observed during my music classes.